Cylinder by cylinder engine modeling of single cylinder 4 stroke engine for control system development - Hasfazri, Abdul Rahman (2012)
The objective of this thesis is to design and simulate cylinder by cylinder engine model for control oriented study based on single cylinder four stroke engines, which combines both physical formulae, such as engine geometries, and empirical formulae. The engine performance, torque and power is calculated by integrating the pressure inside cylinder within one engine cycle. The importance of this study is to predict the engine performance parameters such as indicated work, brake power, and torque that provided with air fuel ratio data and detail geometrical specifications. The model of FZ150i full engine specifications is used for simulation in order to predict the engine performance. The model is simulated between 2000 to 6000 rpm of engine speed range. From this simulation, the result shows that it is almost same with the experimental data by Sitthiracha (2006). Without build the real engine, all the engine performance parameter can be calculated from this simulation, and reduced the time and cost.